DATA ENVELOPMENT ANALYSIS DAN MALMQUIST PRODUCTIVITY INDEX TERHADAP EFISIENSI DAN PRODUKTIVITAS PADA BANK TAHUN 2019 – 2021 - Wirda Hayatun Nupus (Industry Xplore, 2022)
One of the important aspects in measuring banking performance is efficiency, which can be increased by reducing costs in the production process or by increasing profits. Efficiency is one of the factors that can increase productivity. Productivity will measure how much output is produced by Commercial Banks using existing inputs. In measuring efficiency and productivity, commercial banks use inputs in the form of Third Party Funds (DPK), total assets, and operational costs, while the output variables used are financing and operating income. The type of research used in this research is quantitative. Analysis of the data used to measure the level of efficiency using Data Envelopment Analysis (DEA) and to measure the level of productivity of commercial banks using the Malmquist Productivity Index (MPI).